PENINGKATAN KEMAMPUAN SISWA DALAM MENULIS TEKS BERITA DENGAN MODEL PROBLEM BASED LEARNING DAN MEDIA YOUTUBE - ROKHAYATUN ROKHAYATUN (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2023)
This good practice activity is carried out at SMK Negeri 2 Kendal which is located at Jalan Raya Soekarno - Hatta West Kendal. The problem encountered is the low ability of class XI DPIB 1 students in writing news texts. This is because students find it difficult to express ideas, thoughts, or thoughts into writing. One of the students' difficulties in learning to write is writing news texts. In order to overcome these difficulties, one of the efforts that can be made is to use a problem-based learning model and YouTube media. The purpose of this practical activity is to improve students' ability to write news texts. The operational stages of its implementation in class XI DPIB 1 are starting from preliminary activities, core activities, and closing activities. After learning to write news texts using the problem-based learning model and YouTube media, it was found that students who were in very good criteria were 7 people or 20%, while students who were in the good category were around 27 people or 77%, and students in the sufficient category there is one person or 2.9%. The KKTP limit is 75. So, out of a total of 35 students, only one student did not complete, while 34 others were declared complete and reached the specified KKTP. So that it can be said that the problem-based learning model and YouTube media can improve students' ability to write news texts. ABSTRAKKegiatan praktik baik ini dilakukan di SMK Negeri 2 Kendal yang beralamat di Jalan Raya Soekarno - Hatta Barat Kendal. Permasalahan yang ditemui yaitu rendahnya kemampuan siswa kelas XI DPIB 1 dalam menulis teks berita. Hal ini disebabkan karena siswa merasa kesulitan untuk mengungkapkan ide, gagasan, atau hasil pemikiran ke dalam suatu tulisan. Salah satu kesulitan siswa dalam pembelajaran menulis adalah menulis teks berita. Agar kesulitan tersebut dapat diatasi salah satu upaya yang dapat dilakukan adalah menggunakan model problem based learning dan media youtube. Tujuan kegiatan praktik ini dilakukan untuk meningkatkan kemampuan siswa dalam menulis teks berita. Adapun tahapan operasional pelaksanaannya  di kelas XI DPIB 1 adalah mulai dari kegiatan pendahuluan, kegiatan inti,dan kegiatan penutup. Setelah dilakukan pembelajaran menulis teks berita dengan menggunakan model problem based learning dan media youtube diperoleh hasil bahwa peserta didik yang berada pada kriteria sangat baik ada 7 orang atau 20%, sedangkan siswa yang berada dalam kategori  baik ada sekitar 27 orang atau 77%, dan siswa yang berada pada kategori cukup ada satu orang atau 2,9%. Batas KKTP adalah 75. Jadi, dari jumlah total 35 siswa hanya ada satu siswa yang tidak tuntas, sementara 34 lainnya dinyatakan tuntas dan mencapai KKTP yang telah ditentukan. Sehingga dapat dikatakan model problem based learning dan media youtube dapat meningkatkan kemampuan siswa dalam menulis teks berita.